ХОТИН-ҚИЗЛАРНИНГ ЖИСМОНИЙ ТАРБИЯ ВОСИТАСИ СИФАТИДА СОҒЛОМЛАШТИРУВЧИ ГИМНАСТИКА - Улезко, И.В. (SCIENCE and SOCIETY, 2022)
In the presented article questions of the organization and carrying out a post-isometric muscular relaxation and definition of its influence on physical development, are considered physical preparation of women of 24-29 years.